Reasonability of Carrying out Intra-Arterial Selective Chemotherapy (Cisplatin) in Combination with Photodestruction, Brachytherapy and Interferon Therapy in Patients with Uveal Melanoma - Малецький, Анатолій Парфентійович (My University, 2024)
Purpose: To study the effectiveness of selective intra-arterial chemotherapy (SICA) (cisplatin) in combination with photodestruction, brachytherapy (BT) and interferon therapy (IFT) in patients with UM of the eye. Methods: The analysis was carried out in 238 patients (men - 99, women - 139) who received the following treatment methods as organ-preserving treatment for patients with UM: transpupillary thermotherapy (TTT), BT, IFT and SIAC. Results: The results of clinical studies allow us to note that the inclusion of selective intra-arterial chemotherapy (cisplatin) in the complex of organ-preserving treatment of UM made it possible to activate the dynamics of tumour regression after 6 and 12, as well as the reliability in relation to the control group was Р < 0.06 and Р < 0.06, in accordance. It should be noted that the dynamics of tumour regression in the study group (TTT, BT, IFT and SIAC) after two years was more active compared to the control group of patients and complete regression was 39.4%, while in the control group it was 25.7%. The obtained preliminary data on the effectiveness of TTT, BT, IPT and SIAC in patients with UM do not allow us to speak unequivocally about the rational dose of cisplatin and the choice of cytostatic. We can assert the expediency of the chosen approach to complex therapy of UM. Conclusion: Conducting SIAC (cisplatin) in combination with TTT, BT and IFT in patients with UM increases the sensitivity of tumour cells to photodestruction and local radiotherapy, which promotes more active tumour regression.